New possible hetero-holococcolithophore combinations within the genusSyracosphaera - Malinverno, E.; Triantaphyllou, M.; Dimiza, M.; Young, J.R. (Journal of Nannoplankton Research, 2008)
Two new possible hetero-holococcolithophore combinations are shown: Syracosphaera histrica withS. pulchra HOL oblonga type and S. molischii with Gliscolithus amitakareniae. In addition, an ambiguous combination of S. pulchra HOL oblonga type with S. pulchra HOL pirus type is recorded by light-microscope imaging. Although represented by ambiguous combinations, they potentially document new life-cycle associations within coccolithophores to add to the complexity of haplo-diplontic coccolithophore stages.